Creación de un condominio para estudiantes politécnicos de provincias aledañas a la del Guayas. - Delgado Miranda, Andrés Ricardo (2011)
The aim of this study is to collect and analyze all necessary information to determine the feasibility of the creation of a residency for polytechnic students from provinces surrounding Guayas, located in the north of Guayaquil. In this manner an alternative is provided for the lack of appropriate tenement for the students of the university and the rising demand for these services is satisfied. The housing service provided by the condominium is specific to target university students in the Escuela Superior Politecnica del Litoral, youth of both genders, aged between 17 and 24 years, with a socio-economic position medium to high. The project aims to group the services most requested by students who do not live with their families, so that their basic needs can be met comfortably at an affordable price in a single place. The value of the creation of this project is developing a unique option that meets all the services required by young people to meet their needs.